Microwave-Irradiation Induced Fast Simultaneous Extraction of Methoxylated and Hydroxylated Phenolic Compounds from Orthosiphon stamineus Leaves - Sook, Fun Pang; Mei, Zhu Lau; M. M., Yusoff; Jolius, Gimbun (Trans Tech Publications, 2017)
A combined effect of microwave irradiation and solvent types on the phenolic compounds extraction from Orthosiphon stamineus leaves was studied. The effect of as extraction time, the microwave irradiation power and solid to solvent ratio on the extraction yield was studied. Aqueous solvent provides a broader range of polarity than the pure solvent, and hence enabled a simultaneous extraction of both methoxylated and hydroxylated phenolic compounds. It was found that the extraction time of 2 minutes, microwave irradiation power at 300W and 20:1 solvent to solid ratio yielded highest simultaneous extraction of polyphenols (i.e. rosmarinic acid 32.45 mg RA/g DW, sinensetin 261.15 ?g Sin/g DW and eupatorin 2.27 mg Eup/g DW). Result from this work may serve as a useful guide to obtain higher yield of polyphenols from O. stamineus.